2004
DOI: 10.1113/jphysiol.2003.058545
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential stabilization in amphibian skeletal muscle fibres in hypertonic solutions

Abstract: steady-state resting potentials (E m ). Fibres in isotonic Cl− -free, normal and Na + -free Ringer solutions showed similar E m values consistent with previously reported permeability ratios P Na /P K (0.03-0.05) and P Cl /P K (∼2.0) and intracellular [Na + ], [K + ] and [Cl − ]. Increased extracellular osmolarities produced hyperpolarizing shifts in E m in fibres studied in Cl − -free Ringer solution consistent with the Goldman-Hodgkin-Katz (GHK) equation. In contrast, fibres exposed to hypertonic Ringer solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
77
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(95 citation statements)
references
References 44 publications
(96 reference statements)
13
77
5
Order By: Relevance
“…Previous studies have characterised the relationship between cell volume, V c , and membrane potential, E m , in quiescent muscle [9,13,14], and others separately demonstrated that activity alters both V c and E m (e.g. [25,28,30,36]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have characterised the relationship between cell volume, V c , and membrane potential, E m , in quiescent muscle [9,13,14], and others separately demonstrated that activity alters both V c and E m (e.g. [25,28,30,36]).…”
Section: Discussionmentioning
confidence: 99%
“…Relative muscle fibre volumes, V c , were recorded continuously in the superficial fibres of the very thin cutaneous pectoris muscle preparation throughout the experimental protocols using confocal microscope xz-scanning to allow a consistent detection of even small (2-5%) changes in cell volume given established calibration and correction techniques [9]. Measurements were made in the course of and following intermittent low-frequency electric-field stimulation which was chosen as it produces a greater force depression and a slower recovery than high-frequency continuous stimulation [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than encoding hyperosmotic challenge, most channels are activated by hypotonic stimuli and presumed cell swelling, including TrpV4 that is widely expressed in visceral sensory neurons (6,22,32). In contrast, hypertonic stimuli cause hyperpolarization in some cells (16,33) and presumably result in cell membrane shrinkage, contributing to an increased activation threshold for stretch-activated ion channels, consistent with a previous finding that AHS significantly reduced colorectal afferent response frequency and increased response threshold to mechanical stretch (21). The underlying mechanism(s) for short-latency, long-lasting responses of tonic-spiking MIAs and most probing-responsive afferents to AHS remain unresolved and await further study.…”
Section: Chr2mentioning
confidence: 99%